2021
DOI: 10.3389/fphys.2021.729134
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Inflammation Resolution in Arthritis: Current Understanding of Specialized Pro-resolving Lipid Mediators’ Contribution to Arthritis Physiopathology and Future Perspectives

Abstract: The concept behind the resolution of inflammation has changed in the past decades from a passive to an active process, which reflects in novel avenues to understand and control inflammation-driven diseases. The time-dependent and active process of resolution phase is orchestrated by the endogenous biosynthesis of specialized pro-resolving lipid mediators (SPMs). Inflammation and its resolution are two forces in rheumatic diseases that affect millions of people worldwide with pain as the most common experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…mLA resolution is defective in C3H 12/15-LO -/mice Lipoxins and specialized proresolving mediators (SPM) are metabolites of 12/15-LO activity that are well-characterized for their ability to mediate resolution in various models of inflammation, including arthritis (27). We first characterized the expression of Alox15, the gene which encodes 12/15-LO in mice, during the time-course of mLA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mLA resolution is defective in C3H 12/15-LO -/mice Lipoxins and specialized proresolving mediators (SPM) are metabolites of 12/15-LO activity that are well-characterized for their ability to mediate resolution in various models of inflammation, including arthritis (27). We first characterized the expression of Alox15, the gene which encodes 12/15-LO in mice, during the time-course of mLA.…”
Section: Resultsmentioning
confidence: 99%
“…These pro-resolving lipids act through a variety of mechanisms, including inhibition of inflammatory leukocyte recruitment, induction of neutrophil apoptosis and efferocytosis, and reprogramming of macrophages towards a pro-resolving phenotype (42). Previous studies demonstrate a clear role for lipoxins and SPM in regulating inflammation in degenerative or autoimmune arthritis in humans and in mouse models of arthritis (27). Studies in rheumatoid arthritis (RA) patients demonstrated that lower levels of circulating SPM could clearly distinguish active RA patients from healthy controls, indicating a correlation between SPM expression and disease status (32,43).…”
Section: Discussionmentioning
confidence: 99%
“…Current treatments for arthritis have focused on disease control, and the cure still seems unreachable. Therefore, life-long therapy is required to inhibit the inflammatory process to effectively control further cartilage and bone damage ( Zaninelli et al, 2021 ). Arthritis is the leading cause of disability in the United States (US) and other populations ( Basu et al, 2018 ).…”
Section: Sirt1-hmgb1 Axis In Inflammationmentioning
confidence: 99%